2009
DOI: 10.1002/dvdy.21934
|View full text |Cite
|
Sign up to set email alerts
|

Expression of WNT signalling pathway genes during chicken craniofacial development

Abstract: A comprehensive expression analysis of WNT signalling pathway genes during several stages of chicken facial development was performed. Thirty genes were surveyed including: WNT1, 2B, 3A, 4, 5A, 5B, 6, 7A, 7B, 8B, 8C, 9A, 9B, 11, 11B, 16, CTNNB1, LEF1, FRZB1, DKK1, DKK2, FZD1-8, FZD10. The strictly canonical WNTs (2B, 7A, 9B, and 16) in addition to WNT4 WNT6 (both canonical and non-canonical) are epithelially expressed, whereas WNT5A, 5B, 11 are limited to the mesenchyme. WNT16 is limited to the invaginating na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 77 publications
3
69
0
2
Order By: Relevance
“…In particular, WNT5A and WNT5B are prominently expressed in the faces of mouse and chicken (35,81). We showed that RCAS::WNT5A injected into the mandibular prominence leads to beak deviations (70).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In particular, WNT5A and WNT5B are prominently expressed in the faces of mouse and chicken (35,81). We showed that RCAS::WNT5A injected into the mandibular prominence leads to beak deviations (70).…”
Section: Discussionmentioning
confidence: 76%
“…First, WNT11 is locally expressed in the discrete regions of the face (35) and could be mediating facial morphogenesis. Second, WNT11 activates ␤-catenin-independent pathways in the majority of contexts (36), so there is a strong possibility that WNT11 will activate one or more of the these alternative WNT pathways in the face.…”
mentioning
confidence: 99%
“…Signaling by Sonic hedgehog (Hu et al, 2003;Hu and Marcucio, 2009b;Young et al, 2010), Fibroblast growth factor (Richman et al, 1997;Szabo-Rogers et al, 2008Griffin et al, 2013), Bone morphogenetic protein (Francis-West et al, 1994;Duprez et al, 1996;Ashique et al, 2002a,b;Foppiano et al, 2007) and Wnt (Brugmann et al, 2007;Geetha-Loganathan et al, 2009;Reid et al, 2011) all contribute to facial morphogenesis. Our work has focused primarily on the role of the frontonasal ectodermal zone (FEZ) during development of the upper jaw (Hu et al, 2003;Hu and Marcucio, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the WNT signaling pathway in regulating facial morphogenesis is suggested by expression of various WNT ligand genes within the facial prominences (Summerhurst et al, 2008;Geetha-Loganathan et al, 2009). Canonical WNT signaling reporter transgenes such as TopGAL, BATgal and Axin2-lacZ are highly expressed in the facial prominences and their derivatives, further indicating a potential role of WNT/-catenin signaling during facial development (Maretto et al, 2003;Brugmann et al, 2007;Al Alam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%